Frankenstein : Annotated for Scientists, Engineers, and Creators of All Kinds - Shelley, Mary Wollstonecraft, 1797-1851 (Book collections on Project MUSE., 2017)
The original 1818 text of Mary Shelley's classic novel, with annotations and essays highlighting its scientific, ethical, and cautionary aspects.